2020
DOI: 10.1109/access.2020.2974192
|View full text |Cite
|
Sign up to set email alerts
|

Superhighway Virtual Track System Based on Intelligent Road Buttons

Abstract: To improve the safety of superhighways, a virtual track system for superhighways based on intelligent road buttons is studied by means of a structural analysis and mathematical model. The system consists of a road subsystem, onboard subsystem and service center subsystem. When a vehicle equipped with an onboard subsystem nears the road buttons, they activate the virtual track system, and the reader reads location coordinates and road alignment information at that point from the label buttons. At the same time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Clearly, ΔL ≥ 0, and the result calculated by equation ( 25) is larger than that by equation ( 23); hence, equation (25) should be used as an effective control.…”
Section: E Minimum Radius and Length Of Convex Verticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, ΔL ≥ 0, and the result calculated by equation ( 25) is larger than that by equation ( 23); hence, equation (25) should be used as an effective control.…”
Section: E Minimum Radius and Length Of Convex Verticalmentioning
confidence: 99%
“…e superhighway is different from an ordinary highway. To ensure the safety of a superhighway, the pavement of a superhighway is flatter, the route is smoother, and the facilities are more comprehensive [25].…”
Section: E Definition Of a Superhighwaymentioning
confidence: 99%
“…Additionally, the construction cost and use cost of a superhighway once again were studied by us in 2019, and the results showed that the comprehensive cost of a superhighway was higher than that of an ordinary highway and lower than that of a railway, and the economic feasibility of superhighways was again demonstrated [5]. In 2020, to demonstrate the feasibility of superhighways from the perspective of safety, we studied a virtual track technology based on intelligent road buttons, which provided a strong guarantee for the safety of driving on a highway [6]. In the same year, to demonstrate the safety alignment of superhighways, our research team studied the design theory of plane alignment, vertical alignment and cross-section alignment of superhighways based on the linear design theory of ordinary superhighways and the linear design of railways.…”
Section: Research On Superhighwaysmentioning
confidence: 99%